Effects of Doppelgänger Campaigns on Consumer’s Image and Attitudes - Blecha, Adam; San José Iglesias, Rafael; Martínez Pantoja, Yadira Ixchel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
This thesis aims to analyze the influence of Doppelgänger campaigns on consumer perceptions and attitudes towards brands. Doppelgänger campaigns, as forms of cultural jamming, often parody or criticize brands to challenge their public image and authority. Through a mixed-methods approach combining an online survey and empirical data analysis, this study explores the impact of such campaigns on brands represented in three distinct beverage sectors: soft drinks, bottled water, and beer. Participants from varied demographic backgrounds were exposed to both traditional and Doppelgänger brand messages, with their reactions measured to assess changes in brand image and attitude.
Vedoucí práce: Rafael San José Iglesias
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses